Predictive value of apparent diffusion coefficient in evaluation of colorectal carcinoma hepatic metastases' response to radiofrequency ablation. Issue 5 (22nd March 2013) - Szurowska, Edyta; Nowicki, Tomasz K.; Izycka‐Swieszewska, Ewa; Zadrozny, Dariusz; Markiet, Karolina; Studniarek, Michal
<x xml:space="preserve">Abstract</x> Purpose To establish the apparent diffusion coefficient (ADC) suitability to evaluate the radiofrequency ablation (RFA) outcome in patients with chemotherapy resistant or partially responding colorectal adenocarcinoma liver metastases. Materials and Methods A total of 56 patients with 116 metastatic foci over 10 mm in diameter were examined with 1.5 Tesla MRI scanner 1 day before percutaneous RFA treatment. Lesions were evaluated in echo‐planar diffusion‐weighted images with b = 0, 15 and 500 s/mm2. On basis of computed tomography scan at 6 weeks, 3 and 6 months after RFA and serum CEA (carcinoembryonic antigen) level lesion were recognized as responding or nonresponding lesions. ADC values for b = 0–15 and 0–500 s/mm2 of responding and nonresponding lesions were compared. Results Noncomplete ablation concerned 28 lesions. Mean pretreatment ADC values for b = 0–15 and 0–500 s/mm2 of responding metastases were significantly lower (2.14 and 1.48 × 10−3 mm2/s) than those of nonresponding tumors (2.7 and 1.74 × 10−3 mm2/s). Sensitivity, specificity, and accuracy of ADC values for b = 0–15 s/mm2 were 79 (95%CI = 59–92), 85 (95%CI = 76–92), 84%; and for b = 0–500 s/mm2, the efficacy parameters were, respectively, 78 (95%CI = 56–92), 78 (95%CI = 67–86), and 78%. The P value was under 0.001 for both b parameters. Conclusion The pretreatment ADCs values of chemotherapy resistant or partially responding colorectal adenocarcinoma liver metastatic lesion can be predictive factor of tumors response to RFA therapy. J. Magn. Reson. Imaging 2013;38:1027–1032. © 2013 Wiley Periodicals, Inc.